THE EPISTEME OF 'VIRGINITY' IN THE CONTEXT OF FOUCAULT'S PHILOSOPHY. - ONAY-ÇÖKER, Duygu (Academic Journal of Philosophy / Felsefi Düşün)
This study explores the hymen's increased cultural significance, despite its non-functionality, smallness, and inconsequentiality to health. The discourse of virginity gave the hymen its importance and determined how human beings thought, lived, and even why they were killed in the name of its honor. Therefore, this study uses Michel Foucault's philosophy to analyze the body policy of virginity as a subjective way of experience and shows that western culture transforms women into subjects through virginity's discursive and non-discursive practices. This framework enables an analysis of virginity's legitimatization process as a scientific and objective reality that participates in Foucault's conception of the game of truth. In addition, I discuss some shifts in virginity's discursive and scientific practices; the possibility of avoiding this body policy; establishing women's own freedom, and allowing their recreation as a Foucauldian work of art without becoming an object of power. I follow Foucault's methodology, not explaining history in a linear/chronological fashion, but exposing the archaeology of virginity's historical development and transformation.